2011
DOI: 10.1002/art.30645
|View full text |Cite
|
Sign up to set email alerts
|

Use of atorvastatin in systemic lupus erythematosus in children and adolescents

Abstract: Objective Statins reduce atherosclerosis and cardiovascular morbidity in the general population, but their efficacy and safety in children and adolescents with systemic lupus erythematosus (SLE) are unknown. This study was undertaken to determine the 3-year efficacy and safety of atorvastatin in preventing subclinical atherosclerosis progression in pediatric-onset SLE. Methods A total of 221 participants with pediatric SLE (ages 10–21 years) from 21 North American sites were enrolled in the Atherosclerosis P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(122 citation statements)
references
References 50 publications
(76 reference statements)
5
108
0
2
Order By: Relevance
“…Results showed no difference in coronary artery calcium, cIMT, carotid plaque, hsCRP, or markers of endothelial activation. In a similar study with a pediatric population, Schanberg et al [185] showed no effect of atorvastatin on the progression of cIMT over 36 months in patients with JSLE. Post hoc analysis showed some benefit in post-pubertal patients with higher hsCRP.…”
Section: Statinsmentioning
confidence: 94%
“…Results showed no difference in coronary artery calcium, cIMT, carotid plaque, hsCRP, or markers of endothelial activation. In a similar study with a pediatric population, Schanberg et al [185] showed no effect of atorvastatin on the progression of cIMT over 36 months in patients with JSLE. Post hoc analysis showed some benefit in post-pubertal patients with higher hsCRP.…”
Section: Statinsmentioning
confidence: 94%
“…Certain therapeutic 9 approaches, usually with statins, have been implemented for halting subclinical atherosclerosis in lupus patients with inconsistent results [12][13][14][15]. Other preventive strategies, such as ACEIs and ARBs, which have shown a significant benefit in at-risk populations [5], have not been tested in SLE patients.…”
Section: Resultsmentioning
confidence: 99%
“…Кроме того, применение аторвастати-на у педиатрического контингента больных с СКВ в те-чение 36 мес не повлияло на толщину КИМ, хотя уро-вень СРБ и липидный профиль действительно улучша-лись [93].…”
Section: о б з о р ыunclassified